ANALISIS TENTANG HUKUMAN KEBIRI BERDASARKAN UNDANG – UNDANG NOMOR 17 TAHUN 2016 TENTANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANG – UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK MENJADI UNDANG – UNDANG DALAM PERSPEKTIF HAK ASASI MANUSIA - Fattimi Beethoveni Sikumbang; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The issue of pedophiles needs more intensive and serious attention. In protecting the rights of children from rape victims, the Indonesian government through the Republic of Indonesia Law Number 17 of 2016 Application of Government Regulations in lieu of Indonesian Law on Child Protection. This means that Indonesia has legalized the castration penalty for perpetrators of sexual crimes. Castration punishment when linked to human rights (HAM), the castration penalty violates two principles that become the mandate of reform, namely the principle of human rights and democracy.This type of research can be classified into normative legal research, namely legal research conducted by examining library materials. This study examines the subject matter in accordance with the scope and identification of problems through a statute approach carried out by examining the laws and regulations relating to the legal issues examined.Conclusions that can be obtained from the results of the study are the reasons for castration being the choice of the country in the punishment of the offender it is deemed to have a deterrent effect on pedophiles. The ideal form of regulation of punishment for pedophile perpetrators in the perspective of human rights is the Government in the Pancasila mandate, 2 which says that humanity is just and civilized, so that in making a regulation regarding punishment given specifically pedophile perpetrators should be from the aspect of human rights perpetrators, not just talk about adopting existing regulations in other countries. that the ideal punishment for pedophiles is a life sentence, so that not being a predator becomes a deterrent effect for other actors who want to commit the crime.Keywords: Analysis, Castration Punishment, Child Protection, Human Rights